The Emergence of a COVID-19 Related Social Capital: The Case of China. Issue 5 (2nd September 2020) - Bian, Yanjie; Miao, Xiaolei; Lu, Xiaolin; Ma, Xulei; Guo, Xiaoxian
Abstract: This paper develops a new concept called virus-combat social capital and presents relevant findings from a survey of 3009 Chinese WeChat networkers. Virus-combat social capital is defined by the intensity and extensity of social connectedness under conditions of physical isolation during the COVID-19 pandemic. The survey shows that as compared to their counterparts, Chinese people with higher virus-combat social capital consistently do better in both behavioral responses and measures of quality of life.